Urban Policy Entrepreneurship: Activist Networks, Minimum Wage Campaigns and Municipal Action Against Inequality. Issue 4 (July 2023) - Doussard, Marc; Schrock, Greg
Why are cities acting against inequality? We attribute the growth of municipal economic policy to multi-city urban policy entrepreneurship networks. These networks combine activists who create pressure to address inequality with policy experts who supply the legislative means to do so. We illustrate the concept through the Fight for 15 campaign in Seattle and Chicago. Drawing on more than 100 interviews, participant observation and secondary documents, we show that advocates for municipal policy reform use national policy entrepreneurship networks to develop policy-specific and generalized policy advocacy techniques. Centering urban policy entrepreneurship brings into focus three important aspects of current municipal public policy: 1) The two-way interaction between national and local policy campaigns. 2) Partnerships between activists who set the political agenda and policy entrepreneurs who act on political opportunity. 3) The role of national advocacy and policy entrepreneurship networks in converting new policy ideas into routine, off-the-shelf policy solutions.